Mental health symptom burden in elite ice hockey players and its association with self-reported concussive events - Andersson, M. J.; Kenttä, G.; Claesdotter-Knutsson, E.; Håkansson, A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Some studies suggest that elite athletes experience adverse mental health symptoms at rates commensurate with the general population, despite the well-established buffering effects of exercise. Within contact sports, such as ice-hockey, recurrent concussions may be a source of this discrepancy. We compared the point prevalence of various mental health outcomes with other athlete and general population samples, as well as investigated their relationship with concussive events.